Geomorphological dynamics and flood hazards of the Blanquito River (Tafí del Valle, NW Argentina) - Peña Monné, José Luis (2018)
The hazards caused by ravine (quebradas) geomorphological dynamics as consequence of major hydrological events in mountainous areas of Northwest Argentina are little studied. The scarce records for rainfall and river flow are the main limitations. This work provides information about the dynamic functioning of the Blanquito River, located in the Tafí valley (Tucumán province). Starting from a documented flood that occurred in 1987, a geomorphological map was performed by combining images from 1987 and 2016. Field survey, cross-sections of the river course, profile descriptions, radiocarbon datings, and drone surveys were also made to complement map information. The 1987 flooded area was determined estimating the area covered by debris flow deposits. The relatively few mitigation works are also evaluated. Some infrastructures were damaged in the 1987 flood ? such the bridge over 307 Provincial Road, however it is still in use. Urban growth has been substantial and unplanned over the last 30 years and many obstacles were detected in the river course across the town center. Despite the lack of quantitative data with good temporal resolution, a flood hazard map was made that gathers information about several critical points. These locations are susceptible to overflows with different probabilities of occurrence. Finally, mitigation measures are proposed.